Towards a new biological science of language - Bertranpetit, Jaume (Metode Science Studies Journal, 2018)
Science is the human activity aimed at acquiring knowledge by means of a very specific method, the scientific method, in which logical reasoning is put at the service of empirical and observable evidence. We perfectly understand what it means to be able to focus our scientific perspective on a problem: we want to understand it reasonably, according to the observation, and different observers will obtain an equivalent result. More and more fields of knowledge are diving into scientific analysis. Experimental sciences are based on it, but other fields of knowledge have also found themselves needing it in order to gain social acceptance and recognised explanatory possibilities. Jaume Bertranpetit. Institute of Evolutionary Biology. Pompeu Fabra University. Barcelona (Spain).